Translating the essence of healing: Inscription, interdiscursivity, and intertextuality in U.S. translations of Chinese Medicine - Pritzker, Sonya (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper examines the translation of Chinese medicine (CM) texts into English. In what I here call “living translation,” written translation in CM is approached as an ongoing process of reading, writing, communicating, and practicing that works to encode multiple dialogues with past, present and future actors. Translation in this framework is presented as a “conversation in motion,” an unfolding event in which authors draw upon morally grounded notions of medicine, personhood, and self in order to create CM through extended translations. In entering directly into the stream of these conversations, observing how different authors and translators approach the interdiscursivity of CM at the level of textual translation, I discuss the possibilities that this dialogic view of translation opens up for understanding textual translation as a living practice that directly mediates the ways in which CM is practiced in English-speaking populations.